Fibroblasts‐specific p16INK4a exacerbates inflammageing‐mediated post‐infarction ventricular remodelling through interacting with STAT3 to regulate NLRP3 transcription - Xin Gu; Yingqiang Du; Jin'ge Zhang; Jiyu Li; Haiyun Chen; Yujie Lin; Yue Wang; Chunli Zhang; Shiyu Lin; Nannan Hao; Chengyi Peng; Jiacheng Ge; et al. (Clinical and Translational Medicine)
Abstract Background and Aims Inflammageing represents both a critical pathophysiological hallmark and independent risk factor for myocardial infarction (MI), with age‐related increases observed in MI incidence and severity of post‐MI ventricular remodelling. Novel therapeutic strategies targeting inflammageing‐driven mechanisms are urgently required to attenuate adverse ventricular remodelling following MI. This investigation was designed to elucidate the impact of fibroblast‐specific p16INK4a on inflammageing‐associated ventricular remodelling after MI and to develop a targeted nanotherapy to mitigate this process. Methods and Results We found that p16‐mediated inflammageing positively correlated with the severity of post‐infarction ventricular remodelling in patients. POSTN‐driven p16INK4a knockout improved cardiac function, and reduced ventricular remodelling, myocardial inflammation and NLRP3 signalling activation following MI through downregulating STAT3‐mediated NLRP3 inflammasome and upregulating glutathione metabolism pathway in fibroblasts. P16INK4a overexpression induced NLRP3 signalling activation through upregulating NLRP3 transcribed by STAT3 in fibroblasts. In terms of mechanisms, p16INK4a interacted with STAT3, which depended on the SH2 domain of STAT3; P16INK4a promoted the interaction of EZH2 and STAT3, increased the di‐methylation on K49 and phosphorylation on Y705 of STAT3 by EZH2, and promoted NLRP3 transcription through regulating histone modification in the NLRP3 promoter by interfering the formation of Bmi‐1‐EZH2 or Bmi‐1‐BCL6 complex in fibroblasts. Injection of p16INK4a‐accumulated ageing cardiac fibroblasts, or p16INK4a overexpression adenovirus aggravated profibrosis and proinflammation in MI area. However, a novel FH peptide ‘FHKHKSPALSPV’‐neutrophil membrane proteins (NMPs)‐artificial lipid (Li) membranes‐mesoporous silica nanoparticle (MSN) core (FNLM)‐nanocaged p16INK4a‐siRNA, as a newly constructed nanomaterial drug, could prevent post‐infarction ventricular remodelling through inhibiting NLRP3 transcription in targeted cardiac fibroblasts and ameliorating proinflammation and profibrosis. Conclusions P16INK4a drives inflammageing‐mediated post‐MI ventricular remodeling by activating STAT3/NLRP3 signaling in fibroblasts. Targeting p16INK4a via FNLM‐siRNA nanotherapy represents a novel strategy to ameliorate adverse cardiac remodelling, offering translational potential for clinical intervention. Key points Mechanistic Insight: P16INK4a activates NLRP3 transcription via STAT3‐EZH2 crosstalk, disrupting epigenetic complexes (Bmi‐1‐EZH2/BCL6) to exacerbate post‐MI remodelling. Therapeutic Innovation: A fibroblast‐targeted FNLM nanoparticle delivering p16INK4a‐siRNA effectively silences NLRP3, reducing post‐MI inflammageing. Translational Impact: This study identifies p16INK4a‐STAT3 as a druggable axis and proposes FNLM‐p16INK4a‐siRNA as a promising nanotherapy for clinical post‐MI care.